2021
DOI: 10.1371/journal.pone.0246204
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and mental health changes and their vulnerability factors related to COVID-19 lockdown in Italy

Abstract: The COVID-19 pandemic and government imposed social restrictions like lockdown exposed most individuals to an unprecedented stress, increasing mental health disorders worldwide. We explored subjective cognitive functioning and mental health changes and their possible interplay related to COVID-19-lockdown. We also investigated potential risk factors to identify more vulnerable groups. Across Italy, 1215 respondents completed our Qualtrics-based online-survey during the end of a seven to 10-week imposed lockdow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
139
4
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(199 citation statements)
references
References 56 publications
(126 reference statements)
24
139
4
2
Order By: Relevance
“…Most notably, the number of individuals at risk for depression has tripled during lockdowns. With almost half of our sample then falling below the screening cutoff, the reductions in mental well-being, observed across 14 countries, validate and expand available data from other pandemics (3) and early COVID-19 reports [e.g., (6)(7)(8)(9)(10)].…”
Section: Discussionsupporting
confidence: 77%
“…Most notably, the number of individuals at risk for depression has tripled during lockdowns. With almost half of our sample then falling below the screening cutoff, the reductions in mental well-being, observed across 14 countries, validate and expand available data from other pandemics (3) and early COVID-19 reports [e.g., (6)(7)(8)(9)(10)].…”
Section: Discussionsupporting
confidence: 77%
“…A recent study investigated the psychological effects of lockdown on cognitive functions showing general deterioration, in particular regarding concentration and attention (Fiorenzato et al, 2021 ). Difficulties in keeping focused and concentrated could lead to mental fatigue and, consequently, to greater feelings of lockdown pandemic fatigue in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, as lockdown fatigue had been previously related to depressive symptoms (Bartoszek et al, 2020;Field et al, 2021;Seiter and Curran, 2021) and a slowdown in attentional abilities (Fiorenzato et al, 2021), we expected both to be useful in predicting exhaustion due to the restrictive measures in our sample. Furthermore, as mood deflection may be influenced by cognitive dysfunction (e.g., attention deficit; Keller et al, 2019), and physical frailty (Buigues et al, 2015)-particularly gait speed (Marino et al, 2019)-we hypothesized that attentional skills and gait speed would interact in modulating depression mood changes.…”
Section: Introductionmentioning
confidence: 99%
“…High levels of anxiety and depression were also documented in studies from India [155][156][157] , Ecuador 158 , Albania 159 , Ireland 160 , Hungary 88,161 , Spain 162 , Palestine 163 , the UK 164 , Kuwait 165 , Brazil, and Portugal 166 . The prevalence of people reporting clinical depression and anxiety in a sample of 1215 respondents in Italy was recorded to be 32.3% and 35.7%, respectively (compared to 15.39% and 21.40%, respectively, during pre-COVID-19 times) 142 . A similar finding was made by another study from the country 167 .…”
Section: Stressmentioning
confidence: 93%
“…Watching, reading, or listening to the constant stream of COVID-19-related news, perceived health risks 137 , and a perceived lack of autonomy 138 led to increased anxiety among individuals and families in many countries [139][140][141][142][143][144] . The 2020 National Health Interview survey found that US adults were eight times more likely to fit the criteria for serious mental distress during the lockdown as compared to before 145 .…”
Section: Stressmentioning
confidence: 99%